Investigating the influence of design parameters on the indoor environmental quality and thermal comfort in primary schools in Ho Chi Minh City, Vietnam - Le, Thi Ho Vi (2020)
Indoor environmental quality significantly impacts on comfort levels which affect students’ performance and productivity. Currently in Vietnam, very few studies have dealt with the issue, and the current trend is to install energy-intensive air-conditioning in primary schools as this is perceived as more comfortable. In this study, indoor comfort and users’ perceptions were investigated in three primary schools in Ho Chi Minh City during the mid-season (September 2015), the hottest season (April 2016) and the coldest season (December 2016 – January 2017) to provide a good overview. In-situ spot and long-term measurements were recorded. Questionnaires were completed by 4411 children (age range from 8 to 11 years) and 116 teachers to inform the study about their experiences and the extent of their interaction with the buildings in 124 classrooms. The results were analysed by correlating the conditions measured and the comfort votes on a seven-point scale.